2017
DOI: 10.1093/alcalc/agx060
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Drinkers and the Potential Impact of Minimum Unit Pricing—No Single or Simple Effect?

Abstract: From drink purchasing data of heavy drinkers, we estimated the impact of legislating £0.50 minimum unit price. Over two thirds of drinkers, representing all multiple deprivation quintiles, were predicted to decrease alcohol purchasing; remainder, hypothetically, could maintain consumption. Our data address an important gap within the evidence base informing policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…Although we partially controlled for lack of actual consumption data by looking at mean number of purchases over time,30 we acknowledge that heavy drinkers, particularly male drinkers or those with no fixed address or living in communal establishments, are likely to be under-represented in household panel data,5152 and that alcohol purchases are under-reported in general in these datasets 53. For example, compared with the UK Living Costs and Food Survey, KWP households tend to have lower incomes, are more likely to be female headed (as main or primary shoppers), and their expenditure on certain commodity items, including alcohol, tends to be lower 54.…”
Section: Discussionmentioning
confidence: 99%
“…Although we partially controlled for lack of actual consumption data by looking at mean number of purchases over time,30 we acknowledge that heavy drinkers, particularly male drinkers or those with no fixed address or living in communal establishments, are likely to be under-represented in household panel data,5152 and that alcohol purchases are under-reported in general in these datasets 53. For example, compared with the UK Living Costs and Food Survey, KWP households tend to have lower incomes, are more likely to be female headed (as main or primary shoppers), and their expenditure on certain commodity items, including alcohol, tends to be lower 54.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies yield similar results, showing that the major impact of MUP is on heavy drinkers. 57,58,60 These modelling studies suggest that alcohol-attributable health inequalities would fall by a greater amount under MUP than tax changes. 59 MUP has already been implemented in several countries including Russia, Canada, Kyrgyzstan, Republic of Moldova, Ukraine, Belarus and more recently in the Northern Territory of Australia and in Scotland.…”
Section: Pricing Policiesmentioning
confidence: 90%
“…In different societies such as England, Scotland and Ireland, patients with alcohol-related cirrhosis consume mainly cheap alcohol. [56][57][58] Different studies and model-based reports, mainly within the UK population, have shown a clear impact of increasing the MUP on ALD reduction. 59 A recent report from the Welsh government compared the effects of tax cuts and MUP across different populations.…”
Section: Pricing Policiesmentioning
confidence: 99%
“…Although quality control and compliance for the purchase data are regularly monitored by Kantar, with households only included in the final data set if they adhere to pre-assigned quality control criteria (meeting thresholds for data recording and purchasing volume or spend (based on household size) every four weeks), the data have limitations. Heavy drinkers, particularly male drinkers or those with no fixed address or living in communal establishments, are likely to be under-represented in household panel data [ 31 , 32 ] and that alcohol purchases are under-reported in general in these datasets [ 33 ]. For example, compared with the UK Living Costs and Food Survey, KWP households tend to have lower incomes, are more likely to be female headed (as main or primary shoppers), and their expenditure on certain commodity items, including alcohol, tends to be lower [ 34 ].…”
Section: Discussionmentioning
confidence: 99%